Klasifikasi impaksi caninus rahang atas pada pemeriksaan radiograf panoramik dan CBCT sebagai penunjang odontomy - Ika Rachmawati; Ria Noerianingsih Firman (Ikatan Radiologi Kedokteran Gigi Indonesia, 2020)
Objectives: To assess the difficulty level of dental impaction treatment. This article discusses the problem of odontomy treatment based on the classification of maxillary canine impaction through panoramic radiograph examination and CBCT. Literature Review: Impacted tooth is pathological where the tooth fails to reach its normal functional position. Impaired maxillary canine second order placement after impact of third molars. The location of impacted jaw canine teeth most often occurs in the palatal region with a horizontal position according to the maxillary sinus and nasal cavity so that complications are required during odontomy. Conclusion: Based on this literature study, classification on impacted maxillary canine teeth has been developed based on panoramic (2D) and CBCT (3D) radiography, so thus resulting in a complete classification of impacted maxillary canine teeth and can be used as a predictor of the difficulty level of maxillary canine tooth impaction treatment.